Consumption Innovations and Income Innovations: The Case of the United Kingdom and Germany - Weissenberger, Edgar (The Review of Economics and Statistics, 1986)
The present paper is a time series analysis of the relationship between consumption and income innovations. The empirical findings based on aggregate, seasonally unadjusted quarterly UK and German data suggest that the adjustment of consumption to income innovations is not instantaneous (within a quarter), and that the estimated marginal propensities to consume out of income innovations are too large to be compatible with the predictions of the rational expectations-life cycle model. It is found that the same qualitative results are obtained when the disposable income data for West Germany is disaggregated into labour income, transfer payments and profits (transferred from the business sector to households).